2023
DOI: 10.1002/adsr.202300033
|View full text |Cite
|
Sign up to set email alerts
|

Force Sensing and Feedback System Based on Novel Triaxial Force Capacitive Sensor for Minimally Invasive Surgical Robot

Abstract: Minimally invasive surgery has attracted great attention due to small trauma, light pain, and quick recovery. Currently, most minimally invasive surgical robots lack the ability to force sense, resulting in high risks. Herein, a novel minimally invasive surgical force sensing and feedback system for minimally invasive surgical robot is proposed based on a flexible triaxial force capacitive sensor array. The capacitive force sensors utilize a microstructure electrode and orthogonal triangular pyramid microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…[24][25][26][27][28][29][30] Zhang et al have reported a capacitive tri-axis force sensor with microstructures for invasive surgical applications. [31] And the tri-axis force sensor reported by Won et al can even measure temperature and bending angle. [32] Besides, Chen et al [33] have reported another combined structure using three piezoresistive sensing elements, which has similar sensing principle to the four elements' sensor using differential signals, and the capacitive sensor based on this threeelements structure has also been reported by Gu et al [34] Except for this commonly used multielements distributed structure, other structures for tri-axis force sensing have also been reported, [35][36][37][38] and some of them can even detect the force moment.…”
mentioning
confidence: 99%
“…[24][25][26][27][28][29][30] Zhang et al have reported a capacitive tri-axis force sensor with microstructures for invasive surgical applications. [31] And the tri-axis force sensor reported by Won et al can even measure temperature and bending angle. [32] Besides, Chen et al [33] have reported another combined structure using three piezoresistive sensing elements, which has similar sensing principle to the four elements' sensor using differential signals, and the capacitive sensor based on this threeelements structure has also been reported by Gu et al [34] Except for this commonly used multielements distributed structure, other structures for tri-axis force sensing have also been reported, [35][36][37][38] and some of them can even detect the force moment.…”
mentioning
confidence: 99%